ТЕОРЕТИЧНІ ОСНОВИ КОМУНІКАТИВНО-ДІЯЛЬНІШОГО ПІДХОДУ ДО НАВЧАННЯ МОВИ (Педагогіка вищої та середньої школи, 2022)
The article deals with theoretical problems of the approach aimed at enhancing communicative compétence while teaching languages. It also clarifies the rôle of communicative situations in forming communicative compétence.